PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009 – 2014 - Azhari "; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to examine the persial and simultaneous effect of dividend policy, debt policy, and profitability to the value of the company. Where independent variable in this research is dividend policy, debt policy, and profitability while dependent variable is company value. The sample used is secondary data derived from the financial statements of mining manufacturing companies listed on the Indonesia Stock Exchange (IDX) period 2009 to 2014.This study uses secondary data from the company's financial statements. Samples and sampling using purposive sampling technique. The classical assumption test in this research includes normality test, multicollinearity test, heterokedastisity test and autocorrelation test. Data analysis using multiple linear regression analysis, t test, F test, and test of coefficient of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate that parliamentary variables persial (t test) does not affect the PER on manufacturing companies listed on the Indonesia Stock Exchange, while the DER and ROE variables affect the PER of mining manufacturing companies listed on the Indonesia Stock Exchange. The simultaneous test results (f) show the significant influence of DPR, DER, and ROE variables on PER on mining manufacturing companies listed on the Indonesia Stock Exchange.Keywords : Dividend policy, debt policy, profitability, and value compan